2020
DOI: 10.3390/insects11050266
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress, Endoparasite Prevalence and Social Immunity in Bee Colonies Kept Traditionally vs. Those Kept for Commercial Purposes

Abstract: Commercially and traditionally managed bees were compared for oxidative stress (superoxide dismutase (SOD), catalase (CAT), glutathione S-transferase (GST) and malondialdehyde (MDA)), the prevalence of parasites (Lotmaria passim, Crithidia mellificae and Nosema ceranae/apis) and social immunity (glucose oxidase gene expression). The research was conducted on Pester plateau (Serbia—the Balkan Peninsula), on seemingly healthy colonies. Significant differences in CAT, GST and SOD activities (p < 0.01), and MDA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 69 publications
0
12
0
Order By: Relevance
“…This probably corresponds with a high density of bee colonies in the landscape [92] because the number of bee colonies per km 2 in the Czech Republic is one of the highest in the world (>8 honey bee colonies/km 2 ) [93]. According to these results, Taric [94] also found a higher parasitic burden in commercially kept colonies than traditionally kept colonies, which are mostly situated in natural areas. The richness of individual pathogens was in the same trend, where only two eukaryotic pathogens were present in the national parks.…”
Section: Discussionmentioning
confidence: 86%
“…This probably corresponds with a high density of bee colonies in the landscape [92] because the number of bee colonies per km 2 in the Czech Republic is one of the highest in the world (>8 honey bee colonies/km 2 ) [93]. According to these results, Taric [94] also found a higher parasitic burden in commercially kept colonies than traditionally kept colonies, which are mostly situated in natural areas. The richness of individual pathogens was in the same trend, where only two eukaryotic pathogens were present in the national parks.…”
Section: Discussionmentioning
confidence: 86%
“…Conflicting results from different studies can be attributed to many factors, such as the biological characteristics of honey bees (caste, age of the bees, commercially and traditionally managed bees) [31,32], the genetic diversity of honey bees, bee subspecies and lineages [24,[33][34][35], climatic and environmental differences [7,18,36], beekeeping practices [10], as well as diagnostic methods [37] and research conditions (number of analyzed bees, time and method of sampling, natural population research or experiment) [31,38,39]. Nosema species can only be confirmed using molecular methods [39], which can have different levels of resolution, for example, the single-copy Hsp70 gene method qPCR detects a lower amount of N. ceranae copies compared to the multicopy 16S rRNA gene method [37].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the results support our hypothesis that these oxidative stress levels differ between the feral and managed bee colonies. Only a few studies have shown different MDA levels between commercial and traditional colonies in trmka hives without human manipulation, similar to feral colony conditions ( Taric et al 2020 ), which may be an indication of anthropogenic influence or manipulation. The data presented here provide unique information on the life span and oxidative stress of foragers among feral honey bees.…”
Section: Discussionmentioning
confidence: 99%
“…However, the mechanisms underlying this variation have not been elucidated. Specifically, survival advantages during an acute oxidative stress event or the normal life history could be conferred by prevention, repair, or tolerance of the molecular damage ( Guzmán-Novoa et al 1994 ; Rueppell et al 2007 ; Li-Byarlay et al 2016 ; Taric et al, 2019 , 2020 ; Li-Byarlay and Cleare 2020 ). Feral or wild honey bee colonies live in a nonmanaged environment and are under natural selection.…”
mentioning
confidence: 99%